Center-Pivot-Irrigated Dry-Edible Bean Cost-Return Budget in Western Kansas - Dumler, Troy J.; Thompson, Curtis R. (My University, 2006)
This publication projects a budget that reflects expected income and costs based on typical center-pivot-irrigated dry-edible bean production practices in western Kansas.
MF998_2006_10
Keywords: MF999; Economics; Crops; MF